Understanding the Environment: Domestic Violence and Prevention in Urban Aboriginal Communities - Goulet, Sharon; Lorenzetti, Liza; Walsh, Christine; Wells, Lana; Claussen, Caroline (First Peoples Child & Family Review, 2016)
Aboriginal women in Canada are at significantly higher risk for spousal violence and spousal homicide than non-Aboriginal women. Although the majority of Aboriginal people in Canada live in urban settings, there is a dearth of literature focusing on the experiences and violence prevention efforts of urban Aboriginal peoples. In order to understand issues relevant to the prevention of domestic violence among this population, we employed Aboriginal community development principles to conduct a scoping review of the relevant literature to explore the meanings and definitions, risk and protective factors, and prevention/intervention strategies within urban Aboriginal communities. Our study underscores that a number of domestic violence risk and protective factors are present in both Aboriginal and non-Aboriginal communities. However, the multifaceted impacts of colonization, including residential school trauma is a key factor in understanding domestic violence in urban Aboriginal contexts. The limited available research on this topic highlights the need for Aboriginal-led research directed towards eliminating the legacy of violence for Aboriginal peoples in Canada.